Nanosilica synthesized by green synthesis using pineapple peel extract and a preparation method thereof
Patent Information
- Application Number
- CN202610422297.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-01
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-04-01
AI Technical Summary
菠萝果皮富含天然化学物质,如维生素C、类胡萝卜素、花青素、生物碱、酚类和类黄酮等,具有抗菌、抗氧化和抗癌等生物活性,因此菠萝皮可以作为抗氧化剂、抗菌剂,在纳米材料的合成过程中具有良好的绿色合成潜力;但目前尚未见利用菠萝皮提取物进行纳米二氧化硅绿色合成的相关研究报道
本发明以菠萝皮提取物为原料,采用绿色合成技术成功合成了纳米二氧化硅(SiO2NPs)。以该方法制备的SiO2NPs呈球形,平均粒径约为20 nm,SiO2NPs表面附着有来源于菠萝皮提取物中活性物质的官能团,具有良好的分散性和稳定性;并且,SiO2NPs溶液样品具有优异的抑菌活性。因此,绿色合成的SiO2NPs可作为一种无毒、低成本的功能性材料,应用于保鲜、食品包装、生物医学等领域,具有重要的实际意义和广阔的应用前景。
Smart Images

Figure CN122079182B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of green synthesis technology, and in particular to a method for green synthesis of nano-silica using pineapple peel extract. Background Technology
[0002] In recent years, nano-silica (SiO2NPs) has attracted much attention due to its wide range of applications. Silica is an inorganic polar molecule with a silanol group on its surface, which can be modified to exhibit high activity. Furthermore, silica has advantages such as being environmentally friendly, easy to prepare, non-toxic, biosafe, and highly biocompatible, making it a promising candidate for applications in the biological field.
[0003] Currently, SiO2NPs are mainly synthesized using physical and chemical methods, but these methods have many problems, such as high production costs and environmental pollution. In recent years, researchers have begun to study green synthesis methods for SiO2NPs. Green synthesis generally refers to the biosynthesis of nanomaterials using microorganisms, algae, and plants. Compared with physical and chemical synthesis methods, green synthesis methods have better biocompatibility and environmental friendliness, lower costs, mild and controllable synthesis conditions, and antioxidant and antibacterial properties. Currently, some studies have been reported on the green synthesis of nano-silica using plant extracts. However, extracts from different plant sources show significant differences in active ingredient composition, reducing power, and stabilization effects, directly affecting the particle size distribution, morphological characteristics, and bioactivity of the synthesized nano-silica.
[0004] Pineapple[ Ananas comosus [L.) Merr.] is a perennial monocotyledonous evergreen herbaceous plant belonging to the genus *L.* of the family Bromeliaceae. It is the third most important fruit in tropical regions worldwide and one of the most distinctive tropical fruits in my country. Pineapple fruit is rich in nutrients and has a unique flavor, making it very popular with consumers. Pineapples can be eaten fresh or processed into canned goods, juice, and jam, but this process also produces a large amount of byproducts such as peels and pomace, which are usually discarded as waste, causing environmental problems in pineapple-producing areas. Pineapple peels are rich in natural chemical substances, such as vitamin C, carotenoids, anthocyanins, alkaloids, phenols, and flavonoids, possessing antibacterial, antioxidant, and anticancer biological activities. Therefore, pineapple peels can be used as antioxidants and antibacterial agents, and have good potential for green synthesis in the synthesis of nanomaterials; however, there are currently no research reports on the green synthesis of nano-silica using pineapple peel extracts. Summary of the Invention
[0005] The purpose of this invention is to provide a green synthesis of nano-silica using pineapple peel extract and its preparation method, so as to realize the high-value utilization of pineapple peel.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing nano-silica, comprising the following steps: (1) Mix pineapple peel powder and water, and extract to obtain pineapple peel extract; (2) Pineapple peel extract, silicon source and acid are mixed and reacted to obtain nano-silica.
[0007] Optionally, the ratio of pineapple peel powder to water is 1:5~15 (g / mL).
[0008] Optionally, the extraction temperature is 70~90 ℃, and the extraction time is 1~2 h.
[0009] Optionally, the silicon source is tetraethyl orthosilicate; the purity of the tetraethyl orthosilicate is 99%.
[0010] Optionally, the volume ratio of the pineapple peel extract to the silicon source is 2 to 4:1.
[0011] Optionally, the acid in step (2) is hydrochloric acid; the mass fraction of the hydrochloric acid is 36~38%; and the volume ratio of the silicon source to the acid is 4~8:1.
[0012] Optionally, the reaction temperature is room temperature, the reaction time is 2-4 h, and the stirring speed during the reaction is 500-600 rpm.
[0013] Optionally, after the reaction in step (2) has been carried out for 2 to 4 hours, anhydrous ethanol is added to terminate the reaction.
[0014] The present invention also provides nano-silica prepared by the above-mentioned method for preparing nano-silica.
[0015] Compared with the prior art, the present invention has the following beneficial effects: This invention successfully synthesized nano-silica (SiO2NPs) using pineapple peel extract as raw material via a green synthesis technique. The SiO2NPs prepared by this method are spherical with an average particle size of approximately 20 nm. The surface of the SiO2NPs is coated with functional groups derived from the active substances in the pineapple peel extract, exhibiting good dispersibility and stability. Furthermore, the SiO2NPs solution sample demonstrates excellent antibacterial activity. Therefore, the greenly synthesized SiO2NPs can serve as a non-toxic, low-cost functional material for applications in preservation, food packaging, and biomedicine, possessing significant practical value and broad application prospects. Attached Figure Description
[0016] Figure 1 The UV-Vis image of the SiO2 NPs prepared in Example 1; Figure 2 SEM image of SiO2 NPs prepared in Example 1; Figure 3 The infrared spectrum of SiO2NPs prepared in Example 1; Figure 4 The antibacterial activity of SiO2NPs prepared in Example 1 against Escherichia coli is shown in the figures, where (a) is the negative control, (b) is 5 mg / L, (c) is 10 mg / L, and (d) is 20 mg / L. Detailed Implementation
[0017] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0018] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0019] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0020] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be obvious to those skilled in the art. This application specification and embodiments are merely exemplary.
[0021] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0022] The room temperature mentioned in this invention is calculated as 25±2℃.
[0023] All raw materials used in this invention can be obtained commercially or prepared using existing technologies.
[0024] This invention provides a method for preparing nano-silica, comprising the following steps: (1) Mix pineapple peel powder and water, and extract to obtain pineapple peel extract; (2) Pineapple peel extract, silicon source and acid are mixed and reacted to obtain nano-silica.
[0025] In this invention, the active substances in the pineapple peel extract adhere to the surface of the synthesized SiO2NPs. These active substances not only play a reducing role during the synthesis of SiO2NPs, but also adsorb onto the surface of the nanoparticles after synthesis, increasing their surface polarity, thereby enabling the SiO2NPs to be stably dispersed in the aqueous solution.
[0026] In step (1) of this invention, distilled water is added to pineapple peel powder, and extraction is carried out by water bath heating and magnetic stirring. After extraction, the mixture is cooled to room temperature, and the supernatant is collected by centrifugation. The final supernatant is the pineapple peel extract.
[0027] In some embodiments of the present invention, the centrifugation speed is 8000 r / min and the centrifugation time is 10 min, preferably the extracted reactants are centrifuged three times.
[0028] This invention does not impose any special restrictions on the selection of pineapple peel powder; any pineapple peel powder obtained by drying pineapple peel and then making it into powder form is acceptable.
[0029] In some embodiments of the present invention, the pineapple peel powder is prepared by washing fresh pineapple peel with water to remove impurities, then rinsing it three times with distilled water, drying the washed pineapple peel in a vacuum drying oven at 50 ℃, and grinding it into powder to obtain pineapple peel powder.
[0030] In this invention, the ratio of pineapple peel powder to water is 1:5~15 (g / mL), for example, it can be 1:5 (g / mL), 1:8 (g / mL), 1:10 (g / mL), 1:12 (g / mL) or 1:15 (g / mL).
[0031] In this invention, the extraction temperature is 70~90℃, for example, it can be 70℃, 75℃, 80℃, 85℃ or 90℃, etc., and the extraction time is 1~2 h, for example, it can be 1 h, 1.5 h or 2 h, etc.
[0032] Step (2) of this invention involves adding pineapple peel extract to a silicon source, stirring evenly at room temperature, adding acid, continuing to stir and react for a period of time, then adding anhydrous ethanol to terminate the reaction. The resulting precipitate is washed multiple times with anhydrous ethanol and distilled water, centrifuged, and dried to obtain nano-silica.
[0033] In some embodiments of the present invention, the centrifugation speed is 8000 r / min and the centrifugation time is 15 min.
[0034] In some embodiments of the present invention, the drying temperature is 80 °C and the time is 10 h.
[0035] In this invention, the silicon source is tetraethyl orthosilicate; the purity of the tetraethyl orthosilicate is 99%.
[0036] In this invention, the volume ratio of the pineapple peel extract to the silicon source is 2 to 4:1, for example, it can be 2:1, 3:1 or 4:1.
[0037] In this invention, the acid in step (2) is hydrochloric acid; the mass fraction of the hydrochloric acid is 36~38%; the volume ratio of the silicon source to the acid is 4~8:1, for example, it can be 4:1, 5:1, 6:1, 7:1 or 8:1, etc.
[0038] In this invention, the reaction temperature is room temperature, the reaction time is 2-4 hours, for example, 2 hours, 3 hours or 4 hours, and the stirring speed during the reaction is 500-600 rpm, for example, 500 rpm, 550 rpm or 600 rpm.
[0039] In this invention, after the reaction in step (2) has been carried out for 2 to 4 hours, anhydrous ethanol is added to terminate the reaction; the volume ratio of the silicon source and anhydrous ethanol is 1 to 2:1, for example, it can be 1.25:1, 1.5:1, 1.8:1 or 2:1, etc.
[0040] The present invention also provides nano-silica prepared by the above-mentioned method for preparing nano-silica.
[0041] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0042] Example 1 (1) Preparation of pineapple peel extract First, wash the fresh pineapple peel with water to remove impurities, then rinse three times with distilled water. Dry the washed pineapple peel in a vacuum drying oven at 50 ℃, then grind it into powder for later use. Add 10 g of pineapple peel powder to 100 mL of distilled water, heat in a water bath at 80 ℃ with magnetic stirring for 1 h, then cool to room temperature. Centrifuge at 8000 r / min for 10 min, collect the supernatant, and repeat the centrifugation three times to obtain the pineapple peel extract, which is then stored in a refrigerator at 4 ℃ for later use.
[0043] (2) Preparation of SiO2NPs Take 50 mL of pineapple peel extract and add it to 25 mL of tetraethyl orthosilicate (TEOS). Stir magnetically at room temperature until homogeneous, then add 5 mL of 36–38% hydrochloric acid. Continue stirring for 2 h, then add 20 mL of anhydrous ethanol to terminate the reaction. The stirring speed during the reaction is 500–600 rpm. Centrifuge the reaction solution at 8000 r / min for 15 min. Wash the precipitate repeatedly with anhydrous ethanol and distilled water, centrifuge, and then dry in a vacuum oven at 80 ℃ for 10 h to obtain SiO2NPs.
[0044] Test Example 1 Analysis and characterization of SiO2NPs The optical properties of green-synthesized SiO2NPs were analyzed using UV-Vis spectroscopy, scanning in the range of 200–700 nm. The morphological characteristics of the SiO2NPs were observed using scanning electron microscopy (SEM). Fourier transform infrared spectroscopy was used to record data from 4000–400 cm⁻¹. -1 The spectral information of the sample within the wavenumber range is used to characterize the functional group compounds of the sample.
[0045] Figure 1 The UV-Vis spectra of SiO2NPs synthesized in the green manner mediated by pineapple peel extract were characterized in the range of 200-700 nm. The results showed an absorption peak at 238 nm, which is a typical characteristic absorption peak of SiO2.
[0046] The size and morphology of the green-synthesized SiO2NPs were characterized using SEM. Figure 2 As can be seen, the nanoparticles are mostly spherical with a relatively uniform particle size, with an average particle size of about 20 nm. There are very few particle agglomerations, which may be related to the chemical substances in the pineapple peel extract, which increases its stability.
[0047] FTIR was used to detect SiO2NPs and analyze the interaction between chemical substances and nanoparticles in pineapple peel extract. Figure 3 As shown, the sample is located at 796 cm. -1 and 1082 cm -1 The peaks at 457 cm⁻¹ represent the symmetric stretching vibration peak and the asymmetric stretching vibration peak of the Si-O-Si bond, respectively. -1 642 cm -1 and 947 cm -1 The peak at [value missing] is attributed to the presence of symmetrical Si-O bonds and the stretching vibration of Si-O in the green-synthesized SiO2 NPs. These are typical characteristic absorption peaks of SiO2, indicating that the sample is composed of SiO2. Other peaks, such as [value missing] at 3419 cm⁻¹, are also observed. -1 and 1643 cm -1The peaks at these locations correspond to the presence of hydroxyl (-OH) and carbonyl (-C=O) groups, respectively. It can be inferred that these organic groups originate from chemical substances in the pineapple peel, such as polyphenols, flavonoids, and polysaccharides. This indicates that the active substances in the pineapple peel extract adhere to the surface of the synthesized SiO2NPs. These active substances not only play a reducing role during the synthesis of SiO2NPs but also adsorb onto the surface of the nanoparticles after synthesis, increasing their surface polarity and thus enabling them to be stably dispersed in aqueous solution. This is also confirmed in the SEM images.
[0048] Test Example 2 Antibacterial activity assay Antibacterial activity was determined using the filter paper disc diffusion method. *E. coli* was inoculated into LB broth and incubated at 37°C for 24 h. The OD of the bacterial culture was then measured. 600 Dilute to 1.0 and set aside. Pour 20 mL of LB solid medium into a petri dish, let it solidify, then add 100 µL of bacterial suspension and spread evenly with a spreader. Then place circular filter paper discs (6 mm in diameter) that have been soaked in different concentrations (5 mg / L, 10 mg / L, 20 mg / L) of SiO2NPs solution and air-dried. Incubate at 37 ℃ for 24 h, measure the diameter of the inhibition zone, and analyze the antibacterial ability of SiO2NPs. Three replicates were set up for each concentration. The negative control contained only growth medium and was incubated in purified water to eliminate the water with antibacterial effect.
[0049] The results showed that SiO2NPs had an effective inhibitory effect on Escherichia coli after being cultured at 37 ℃ for 24 h. Figure 4 The transparent region indicates that SiO2NPs can inhibit bacterial growth. At low concentrations, the antibacterial effect is positively correlated with the concentration of SiO2NPs. The optimal condition for the antibacterial activity of SiO2NPs against Escherichia coli is a concentration of 10 mg / L, where the inhibition band diameter is the largest. However, when the concentration of SiO2NPs increases to 20 mg / L, the diameter of the inhibition band decreases, indicating a decline in antibacterial activity.
[0050] In summary, SiO2NPs were synthesized using pineapple peel extract as a raw material via a green synthesis technique. The successful synthesis of SiO2NPs was confirmed by UV-Vis and FTIR spectroscopy. SEM observation revealed that the SiO2NPs were spherical with an average particle size of approximately 20 nm. FTIR spectroscopy also showed that the surface of the SiO2NPs contained functional groups derived from the active substances in the pineapple peel extract, which may have played a reducing and stabilizing role in the green synthesis process. The 10 mg / L SiO2NPs solution exhibited the greatest antibacterial activity against *Escherichia coli*. Therefore, green-synthesized SiO2NPs show great promise as a non-toxic, low-cost alternative for applications in food preservation, food packaging, and biomedicine.
[0051] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing nano-silica, characterized in that, Includes the following steps: (1) Mix pineapple peel powder and water, and extract to obtain pineapple peel extract; (2) Pineapple peel extract, silicon source and acid are mixed and reacted to obtain nano-silica; The volume ratio of the pineapple peel extract to the silicon source is 2~4:1; The acid in step (2) is hydrochloric acid; the mass fraction of the hydrochloric acid is 36~38%; the volume ratio of the silicon source to the acid is 4~8:1; The reaction was carried out at room temperature for 2-4 hours, with a stirring speed of 500-600 rpm.
2. The method for preparing nano-silica according to claim 1, characterized in that, The ratio of pineapple peel powder to water is 1:5~15 (g / mL).
3. The method for preparing nano-silica according to claim 1, characterized in that, The extraction temperature is 70~90℃, and the extraction time is 1~2 h.
4. The method for preparing nano-silica according to claim 1, characterized in that, The silicon source is tetraethyl orthosilicate; the purity of the tetraethyl orthosilicate is 99%.
5. The method for preparing nano-silica according to claim 1, characterized in that, After the reaction in step (2) has been going on for 2 to 4 hours, anhydrous ethanol is added to terminate the reaction.
